(untitled) (Asian Journal of Social Science Studies, 2022)
The male gaze is one of the main critical focuses in feminist critical theory. The heroine of "A Lost Woman", Mrs. Forrester, is a degenerate woman in the eyes of the narrator Niel Herbert. But in fact, the author, Willa Cather, always attempts to reduce the influence of the male gaze on her during the writing process. This article analyzes the limitations of Niel’s views on Mrs Forrester’s femininity, emotional world, and rebellion against tradition by highlighting the complexity of Mrs Forrester’s image. Through employing more different eyes, men’s stereotyped perceptions on women are subverted, which further reflects feminist consciousness against traditional male discourse.